P-032 Vitamin D in African Americans with Inflammatory Bowel Disease. (March 2016) - Barrow, Jasmine; Limketkai, Berkeley; Hou, Jason; Isaacs, Kimberly; Kuemmerle, Jay; Brant, Steven
Abstract : Background: Lower vitamin D levels, in the form of 25(OH)D have been established as associated with inflammatory bowel disease (IBD) in Caucasian populations. Vitamin D is thought to play an immunoregulatory role in (IBD). We conducted a case-control study to compare vitamin 25(OH)D levels in African Americans with IBD to matched African American controls. Methods: Sera was obtained from patients with confirmed IBD and their spouse or friend controls recruited by the IBD Centers of the Multicenter Atlantic African-American Inflammatory Bowel Disease Study (MAAAIS), coordinated by the Johns Hopkins Genetics Research Center of the NIDDK IBD Genetics Consortium (IBDGC). Diagnoses of Crohn's disease, ulcerative colitis or IBDU were confirmed by review of medical records, and phenotypes of disease site and behavior were per the IBDGC phenotyping manual. All participants were self reported African Americans. Data was analyzed using the paired t -test, and the McNemar test. Crohn's disease cases were analysed with logistical regression to obtain odds ratios (OR). Results: Ninety cases and 90 matched controls were evaluated. One case with 25(OH)D >100 ng/mL was excluded, leaving 89 matched pairs for analyses. Cases and controls had similar mean age (42.4 ± 15.3 and 42.9 ± 15.9 years), but differed by sex. There were 26 male cases and 44 males controls, which was significant ( P = 0.027). Most cases (n = 51) and controls (n = 56) were vitamin D deficient (25(OH)D <20 ng/mL), with no significant difference between the groups ( P = 0.46). Furthermore, there were no significant differences in mean 25(OH)D levels between cases (19.19 ± 9.73 ng/mL) and controls (18.6 ± 8.40 ng/mL) ( P = 0.627). Within Crohn's disease, 25(OH)D levels did not show significant differences by ileal disease site (OR 0.71of 25(OH)D >20 ng/mL, 95% CI 0.20–2.58, P = 0.608. There was a very small trend is seen toward lower 25(OH)D levels in Crohns cases with stricturing (B2) and penetrating (B3) disease compared to non-stricturing, non-penetrating disease (change in 25(OH)D −1.7 ng/mL for B2, −3.6 ng/mL for B3) however, again this was not statistically significant ( P = 0.624, P = 0.342). Conclusions: Recent studies have shown that IBD patients have lower levels of vitamin D, suggesting that vitamin D plays a role in IBD, or the development of IBD may affect vitamin D levels. African Americans have also been shown to have low vitamin D levels. This study shows that while African Americans with IBD have low vitamin D levels, so do their spouses and close friends, who are also African American, with no statistically significant differences by IBD disease status. Lack of difference may be secondary to environmental effects on vitamin D levels in this highly matched cohort. Furthermore, disease location and behavior does not appear to correlate with vitamin D levels in African-American CD patients. Additional analysis in a higher-powered study is warranted.